2005
DOI: 10.1007/bf03168375
|View full text |Cite
|
Sign up to set email alerts
|

Papel del selenio sobre la capacidad antioxidante en ratones tratados con metomil

Abstract: Methomyl carbamate is a pesticide widely used in the control of insects. The present work aims at studying the effect of selenium on the antioxidant system of methomyl-treated mice. Swiss albino mice were intraperitoneally administered a single dose of methomyl (7 mg/Kg body weight). Mice of another group were injected with sodium selenite (5 pmole/Kg b.wt.) 7 days before methomyl intoxication. After 24 hours, methomyl exposure resulted in significant increase in lactic dehydrogenase activity (LDH). The antiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 17 publications
4
14
0
1
Order By: Relevance
“…Recently Mahagoub and Medany [10] reported that chronic exposure of methomyl (17 mg/ kg body wt) for 2 months revealed significantly decreased SDH activity in rat testis. In the present study increase in LDH activity indicates leakage of LDH from tissues due to loss of membrane permeability caused by increased oxidative damage [56,57] or by depletion of ATP [58,59]. In the present study it has been found that increase in the dose and duration of exposure of methomyl caused decrease in the activity of Na + -k + ATPase, Mg ++ ATPase, and Ca ++ ATPase in the testes and epididymis.…”
Section: Discussionsupporting
confidence: 55%
“…Recently Mahagoub and Medany [10] reported that chronic exposure of methomyl (17 mg/ kg body wt) for 2 months revealed significantly decreased SDH activity in rat testis. In the present study increase in LDH activity indicates leakage of LDH from tissues due to loss of membrane permeability caused by increased oxidative damage [56,57] or by depletion of ATP [58,59]. In the present study it has been found that increase in the dose and duration of exposure of methomyl caused decrease in the activity of Na + -k + ATPase, Mg ++ ATPase, and Ca ++ ATPase in the testes and epididymis.…”
Section: Discussionsupporting
confidence: 55%
“…The elevated LDH activity might be due to its leakage in the seminiferous tubular fluid from the germ cells which are damaged by the increased oxidative stress. [ 27 28 ] The increase in the ALP activity may also be attributed to the cellular leakage caused by chemical-induced injury of the tissue. [ 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…Upon postischemic GSH treatment, intravital fluorescence microscopy has demonstrated an almost complete restoration of sinusoidal blood flow, paralleled by a reduction of inflammatory leukocyte adherence in sinusoids and postsinusoidal venules, resulting in reduced necrotic tissue injury and improved rat survival (706). Micronutrients like selenium are observed to enhance the endogenous antioxidant capacity of the cells by increasing the activity of SOD and the GSH content (177). Accordingly, selenite supplementation significantly improves postischemic hepatic microcirculation by acting as a radical scavenger and by preserving the antioxidative capacity of the liver (949).…”
Section: A Antioxidative Antiadhesive and Anti-inflammatory Approamentioning
confidence: 96%